The VITA Project: Heritability of Resistance to Activated Protein C - Tosetto, Alberto; Castaman, Giancarlo; Cappellari, Antonio; Rodeghiero, Francesco (Thrombosis and Haemostasis, 2000)
Resistance to activated protein C (APC) is a risk factor for venous thromboembolism also in absence of the FV Leiden mutation. To evaluate the influence of genetic factors on APC resistance, we evaluated the heritability of the APC resistance phenotype in 1,519 sib-parent pairs randomly selected from the VITA Project. After adjustment for known influencing factors, a high heritability coefficient (0.58) was observed and parental response to APC was the single most important factor in predicting the corresponding phenotype in sibs. In 32 parentsib pairs in which phenotypic resistance to APC unrelated to FV Leiden was present in both parents and sibs, no additional mutation on the 306-aminoacid residue of FV (FV Cambridge and FV Hong Kong) was found. In these 32 parent-sib pairs, FVIII:C and vWf:Ag levels were not significantly increased and there was no excess prevalence of the R2 allele of exon 13 of FV gene. This study suggests that the response to APC is significantly influenced by genetic factors also at a population level, but the responsible mechanisms are still undefined.
Keywords: APC resistance; genetic; Factor V; thrombophilia; epidemiology